2010
DOI: 10.2119/molmed.2010.00008
|View full text |Cite
|
Sign up to set email alerts
|

Early Increase of Plasma Homocysteine in Sepsis Patients with Poor Outcome

Abstract: Moderate hyperhomocysteinemia is a well-established coronary risk factor that develops when dietary supply with folate and/or vitamin B 12 is inadequate. Recently, stimulated peripheral blood mononuclear cells were shown to produce homocysteine. Thus, the stimulated immune system may contribute to moderate hyperhomocysteinemia during certain diseases. Because multiple trauma and sepsis are accompanied by often strong inflammatory responses, we investigated whether hyperhomocysteinemia may develop in patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 35 publications
2
33
0
1
Order By: Relevance
“…Also, homocysteine accumulates in parallel with neopterin upon stimulation of human peripheral blood mononuclear cells, indicating an additional direct link between immune activation and elevated tHcy. This finding is further substantiated by recent observations in sepsis patients, in whom tHcy increased only in nonsurvivors as compared with survivors …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Also, homocysteine accumulates in parallel with neopterin upon stimulation of human peripheral blood mononuclear cells, indicating an additional direct link between immune activation and elevated tHcy. This finding is further substantiated by recent observations in sepsis patients, in whom tHcy increased only in nonsurvivors as compared with survivors …”
Section: Discussionsupporting
confidence: 79%
“…This finding is further substantiated by recent observations in sepsis patients, in whom tHcy increased only in nonsurvivors as compared with survivors. 41…”
Section: Thcy Cellular Immune Activation and Redox Statusmentioning
confidence: 99%
“…2B). Throughout the last decade, it has been shown that the prevalence of HHcy in critically ill patients varies from 16% to 55% [10,14,24,25], taking into account the different reference plasma Hcy levels used (!10 or !15 mmol). In our study we took 15 mmol/L as the hospital reference value, according to normal values considered by the American Heart Association (5e15 mmol/L) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the stimulated immune system may contribute to moderate hyperhomocysteinemia during certain diseases. Multiple trauma and sepsis are often accompanied by strong infl ammatory responses (18) .…”
Section: Introductionmentioning
confidence: 99%